You may simplify the function to its lowest terms, hence you should write the factored forms of numerator and denominator such that:

f(x) = 4x(x-3)/(x+1)(x-3) = 4x/(x+1)

You need to remember that solving the equation f'(x)=0 you may find information about minimum/maximum of function f(x) such that:

f'(x) = (4(x+1)-4x(x+1)')/((x+1)^2)

f'(x) = (4x+4-4x)/((x+1)^2)

...

## See

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

You may simplify the function to its lowest terms, hence you should write the factored forms of numerator and denominator such that:

f(x) = 4x(x-3)/(x+1)(x-3) = 4x/(x+1)

You need to remember that solving the equation f'(x)=0 you may find information about minimum/maximum of function f(x) such that:

f'(x) = (4(x+1)-4x(x+1)')/((x+1)^2)

f'(x) = (4x+4-4x)/((x+1)^2)

f'(x) = 4/((x+1)^2)

Since f'(x) != 0 for any value of x, then the function has no such points as maximum,minimum or inflection points.

The line x=-1 becomes the vertical asymptote to graph of the function as is presented in the sketch below: